Turning tolerogenic into immunogenic ileal cell death through ileal microbiota: the key to unlock the mystery of colon cancer immunoscore?. (1st January 2020) - Roberti, Maria Paula; Picard, Marion; Yonekura, Satoru; Zitvogel, Laurence
ABSTRACT: Why PD-1 blockade is ineffective in the vast majority of colorectal cancers (CCs) lacking microsatellite instability but harboring high densities of tumor infiltrating T cells and follicular T helper (TFH) and B cells remained so far an open conundrum. In a recent report published in Nature Medicine, we bring evidence in mice and patients that ileal microbiota turns tolerogenic apoptosis of ileal intestinal epithelial cells (IEC) into immunogenic cell demise capable of eliciting IL-1β-dependent TFH responses that benefit from anti-PD1 antibodies.